Sudah Bermaknakah Pekerjaan Anda? Peran Kepemimpinan Melayani, Machiavellianisme dan Perilaku Kewargaan-Organisasi - Faneza Raga Galdana; Endang Parahyanti (Psyche 165 Journal, 2023)
After the Covid pandemic storm that hit Indonesia in the last 2 years, it had an impact on business processes in various industrial sectors. The Manufacturing Industry is one of those affected. Reduction in the workforce which has an impact on company effectiveness is one of the impacts. Manufacturing sector workers suffered a lot from this condition, because they were forced to go home and those who were retained could not get a work from home policy. Workers must do jobs that exceed their capacity so that it can have a bad effect. Workers who are indeed retained will still be deducted from their wages and their working hours will increase. Workers are required to work beyond working hours and be able to be sincere and interpret their work, so that they can be maintained by the company. The role of their superiors also lacks personality and good leadership, so they do not understand what their subordinates need. This study aims to examine the relationship between Machiavellian personality and organizational citizenship behavior moderated by servant leadership and meaningful work. The research subjects were 902 respondents in the manufacturing industry aged 20-45 years, with a ratio of 555 men and 347 women who filled out the four measurement scales, namely the servant leadership scale, work meaningfulness scale, Machiavellianism scale, and organizational-citizenship behavior scale. Data collection uses the survey method which is given online using the Google form. Researchers used moderated regression analysis of the Hayes macro process model 2 to test this research model. The results showed that the role of meaningfulness in the workplace can moderate and positively relate to the mach personality trait on organizational citizenship behavior. Meanwhile, the role of servant leadership cannot moderate the relationship between the mach personality trait and organizational citizenship behavior.